Tingkat Pengetahuan Ibu Nifas tentang Kolostrum dengan Motivasi Pemberian Kolostrum di Rumah Sakit Panembahan Senopati Bantul, Yogyakarta - Desti Astuti; Anafrin Yugistyowati; Oktaviana Maharani (Alma Ata University Press, 2015)
In 2012 the scope of exclusive breastfeeding in DIY were 48%, while in Bantul district as much as 62.05% in 2013. Breastfed which is first out after delivery called colostrum and very important given to infants, but many of postpartum mothers are less or not knowing about the importance of colostrum. The purpose of study was to know relationship between the knowledge level of postpartum mothers about colostrum and motivation of giving colostrum in Panembahan Senopati Bantul hospital, Yogyakarta. This study was an observational analytic with cross sectional design. Samples were 54 of postpartum mothers days 0 to 4 at Panembahan Senopati Bantul hospital, Yogyakarta which obtained by accidental sampling technique. Instruments used was closed questionnaire. Data analysis used Kendal Tau test. The data were analyzed by statistical correlation kendall tau obtained p-value were 0.000<α (0.05). The value of a correlation coefficient were 0.632. it mean that the connection was strong. In conclusions, there was a relationship between knowledge level of pospartum mothers about colostrum and motivation of giving colostrum in Panembahan Senopati Bantul hospital, Yogyakarta 2015.